Neurologic Injury in Operatively Treated Acetabular Fractures. Issue 10 (October 2015) - Bogdan, Yelena; Tornetta, Paul; Jones, Clifford; Gilde, Alex K.; Schemitsch, Emil; Vicente, Milena; Horwitz, Daniel; Sanders, David; Firoozabadi, Reza; Leighton, Ross; de Dios Robinson, Juan; Marcantonio, Andrew; et al.
Abstract : Objectives: The purpose of this study is to evaluate a series of operatively treated acetabular fractures with neurologic injury and to track sensory and motor recovery. Methods: Operatively treated acetabular fractures with neurologic injury from 8 trauma centers were reviewed. Patients were followed for at least 6 months or to neurologic recovery. Functional outcome was documented at 3 months, 6 months, and final follow-up. Outcomes included motor and sensory recovery, brace use, development of chronic regional pain syndrome, and return to work. Results: One hundred thirty-seven patients (101 males and 36 females), average age 42 (17–87) years, met the criteria. Mechanism of injury included MVC (67%), fall (11%), and other (22%). The most common fracture types were transverse + posterior wall (33%), posterior wall (23%), and both-column (23%). Deficits were identified as preoperative in 57%, iatrogenic in 19% (immediately after surgery), and those that developed postoperatively in 24%. A total of 187 nerve deficits associated with the following root levels were identified: 7 in L2-3, 18 in L4, 114 in L5, and 48 in S1. Full recovery occurred in 54 (29%), partial recovery in 69 (37%), and 64 (34%) had no recovery. Forty-three percent of S1 deficits and 29% of L5 deficits had no recovery. Fifty-five percent of iatrogenic injuries did not recover. Forty-eight patients wore a brace at the final follow-up, all for an L5 root level deficit. Although 60% (42/70) returned to work, chronic regional pain syndrome was seen to develop in 19% (18/94). Conclusions: Peripheral neurologic injury in operatively treated acetabular fractures occurs most commonly in the sciatic nerve distribution, with L5 root level deficits having only a 26% chance of full recovery. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.